PENGARUH GAYA HIDUP, PERSEPSI RISIKO DAN INCOME TERHADAP MINAT PENGGUNAAN FINTECH (PAYLATER) PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS SLAMET RIYADI - Puji Amimah; Dorothea Ririn Indriastuti (LPPM PoliteknikPratamaKendal- Universitas Sains Dan Teknologi Komputer, 2026)
This study uses a quantitative method which aims to determine the effect of lifestyle, risk perception and income on interest in using paylater. The population used in this study were students of the Faculty of Economics and Business, Slamet Riyadi University, with 96 students as respondents. The sampling technique used probability sampling with stratified random sampling method. The data collection technique used a questionnaire and data processing and hypothesis testing using SPSS 27. The classic assumption test used is multicollinearity test, autocorrelation test, heteroscedasticity test and normality test. The data analysis technique uses multiple linear regression tests, t tests, F tests and R2 tests. The validity test results show that all statement items for lifestyle, risk perception, income and interest in use are valid because the p value <0.05 and reliable because Cronbach alpha> 0.60. The result classical assumption test all variables have passed the multicollinearity test, autocorrelation test, heteroscedasticity test and normality test. The results of multiple linear regression analysis obtained the equation Y = -3.809 + 0.506 X1 + 0.190 X2 + 0.322 X3 + e. The t test results show that lifestyle (X1), risk perception (X2), income (X3) has a significant effect on interest in using paylater. The F test obtained a calculated F value of 129.370 significance of 0.000 <0.05, which means that the regression mode used in this study is correct. The R2 test results show that the contribution of the influence of the independent variables to the dependent variable is 80.2%, the remaining 19.8% is influenced by other factors outside the variables such as financial literacy, perceived benefits and others.